If the roots of 1 0 x 3 − c x 2 − 5 4 x − 2 7 = 0 are in harmonic progression then find c .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I did it by using a different approach but this is the best method ! :)
Let the roots be a 1 , a + d 1 and a + 2 d 1 , then by Vieta's formulas:
⎩ ⎪ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎪ ⎧ a 1 + a + d 1 + a + 2 d 1 = 1 0 c a ( a + d ) 1 + ( a + d ) ( a + 2 d ) 1 + a ( a + 2 d ) 1 = − 5 2 7 a ( a + d ) ( a + 2 d ) 1 = 1 0 2 7 . . . ( 1 ) . . . ( 2 ) . . . ( 3 )
( 2 ) : a ( a + d ) 1 + ( a + d ) ( a + 2 d ) 1 + a ( a + 2 d ) 1 ⇒ a ( a + d ) ( a + 2 d ) a + 2 d + a + a + d a ( a + d ) ( a + 2 d ) 3 ( a + d ) 3 ( a + d ) ( 1 0 2 7 ) ⇒ a + d = − 5 2 7 = − 5 2 7 = − 5 2 7 = − 5 2 7 = − 3 2
( 3 ) : a ( a + d ) ( a + 2 d ) 1 a ( a + d ) ( a + 2 d ) a ( − 3 2 ) ( a + 2 d ) ⇒ a ( a + 2 d ) = 1 0 2 7 = 2 7 1 0 = 2 7 1 0 = − 9 5
( 1 ) : a 1 + a + d 1 + a + 2 d 1 a ( a + d ) ( a + 2 d ) ( a + d ) ( a + 2 d ) + a ( a + 2 d ) + a ( a + d ) a ( a + d ) ( a + 2 d ) ( a + d ) ( a + 2 d + a ) + a ( a + 2 d ) a ( a + d ) ( a + 2 d ) 2 ( a + d ) 2 + a ( a + 2 d ) [ 2 ( − 3 2 ) 2 − 9 5 ] ( 1 0 2 7 ) [ 9 8 − 9 5 ] ( 1 0 2 7 ) 3 1 ˙ ( 1 0 2 7 ) ⇒ c = 1 0 c = 1 0 c = 1 0 c = 1 0 c = 1 0 c = 1 0 c = 1 0 c = 9
Problem Loading...
Note Loading...
Set Loading...
Hint: Use the fact that polynomial equation formed by replacing x with 1/x i.e x-->1/x will have roots in AP.From there it easy considering roots as
a-d,a,a+d then applying vieta to get 'a' (which is a root of the polynomial obtained after transformation and must satistisy it)